Prognostic significance of the lymphocyte-to-monocyte ratio in patients with malignant pleural mesothelioma. Issue 1 (October 2015) - Yamagishi, Tomoko; Fujimoto, Nobukazu; Nishi, Hideyuki; Miyamoto, Yosuke; Hara, Naofumi; Asano, Michiko; Fuchimoto, Yasuko; Wada, Sae; Kitamura, Kenichi; Ozaki, Shinji; Kishimoto, Takumi
Highlights: The LMR is an independent marker of prognosis in patients with malignant pleural mesothelioma. The LMR is superior to the other inflammation-based marker regarding prognostic ability. The LMR is a simple marker and is feasible to predict patient's outcome in routine clinical practice. Abstracts: Objectives: Chronic inflammation plays a key role in the pathogenesis of malignant pleural mesothelioma (MPM) as a result of asbestos exposure. Several inflammation-based prognostic scores including the lymphocyte-to-monocyte ratio (LMR), Glasgow Prognostic Score (GPS), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) reportedly predict survival in many malignancies, while the role of LMR in MPM remains unclear. The aim of this study was to evaluate the clinical value of LMR and to compare the prognostic value of these inflammation-based scores in predicting overall survival (OS) in MPM. Materials and methods: One hundred and fifty patients with histologically proven MPM were included in this retrospective study. Kaplan–Meier curves and multivariate Cox-regression analyses were calculated for OS. The area under the receiver operating characteristics curve (AUC) was calculated to compare the discriminatory ability of each scoring system. Results: An elevated LMR was significantly associated with prolonged OS. Patients with LMR <2.74 had significantly poor survival compared with LMR ≥2.74 (median, 5.0 versus 14.0 months; p  = 0.000). The LMR consistently had a higher AUC value at 6 months (0.722), 12 months (0.712), and 24 months (0.670), compared with other scores. Multivariate analysis showed that the LMR was independently associated with OS. Conclusions: The LMR is an independent prognostic marker for OS in patients with MPM and is superior to other inflammation-based prognostic scores with respect to prognostic ability.